Necroecotheology. Counter-hegemonic hermeneutics in times of pandemic - Toledo Alcalde, José Octavio (2022)
This article approaches the theme of the predatory aims of colonial and neocolonial instrumentalization of christian faith, anthropology, ecology, and politics. This work proposes the neologism necroecotheology and instrumental subjectivity as keys of transdisciplinary interpretation of the human-environmental imbalance, above all in times of planetary crisis such as that which the pandemic imposes on us. In the same way, it shows the inflection point between European secularism and colonial religious subjectivity imposed in invaded lands. Using the works of activists of liberation theology and philosophy, human rights, and related disciplines, the article connects theology, politics and ecology in one platform of analysis, discussion, and proposals of resolute alternatives. The piece concludes with one of these proposals, another neologism, ecosacrality, a counter-hegemonic vision from beyond the christian world, that seeks to re-balance and re-unite the human-environmental relationship.